Intelligent compaction technology for geomaterials: A demonstration project - Correia, A. Gomes (2016)
This chapter seeks to assess the advantages and disadvantages of intelligent Compaction (IC), as well as formulating a comparison with conventional compaction methods in terms of efficiency. This goal was achieved through in situ application of various technologies to two distinct types of material: a soil-rockfill mixture and a sandy soil. Data was obtained and analysed by the IC continuous information, as well as by the application of several different conventional compaction control tests and methods. Results show that the IC technology presents a superior performance, as well as various advantages when compared to conventional compactors. The chapter begins with the description of the demonstration project carried out for that purpose, including two types of geomaterials, available compaction equipments and construction planning. Compaction efficiency of the compactors on both soil-rockfill mixture and soil materials with different thicknesses used in the experimental sections is analyzed through different monitoring devices are presented.